Peranan Service Convenience dalam Meningkatkan Repurchase Intention dan Loyalitas Pelanggan di Bahagia Kopi - Hasna Ruwaidah Nikmatullah; Reni Wijayanti; Iwan Kurniawan; Caesar Octoviandy Purba (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
The concept of service convenience is an important element in the field of marketing. In the food and beverage business, the application of service convenience will maintain long-term relationships and increase consumer confidence. However, there are still many companies that provide unpleasant services to consumers so that many of them feel disappointed and do not want to become regular customers. The purpose of this study was to determine the role of service convenience in increasing repurchase intention and customer loyalty at Bahagia Kopi HQ Banda. The population of this study were consumers of Bahagia Kopi HQ Banda, the sample amounted to 100 consumers. The sampling technique was purposive sampling. The type of research used is quantitative research with data analysis testing using path analysis using the SmartPLS 3.0 program. The results in this study are service convenience plays a significant role in customer loyalty through repurchase intention at Bahagia Kopi HQ Banda. This shows that service convenience is important for Bahagia Kopi HQ Banda to improve because it has a role in motivating consumers of Bahagia Kopi HQ Banda to have repurchase intentions, so as to build customer loyalty to Bahagia Kopi HQ Banda